How does leaf physiological acclimation impact forage production and quality of a warmed managed pasture of Stylosanthes capitata under different conditions of soil water availability? - Habermann, Eduardo; Dias de Oliveira, Eduardo A.; Delvecchio, Gustavo; Belisario, Rafael; Barreto, Rafael Ferreira [UNESP]; Viciedo, Dilier Olivera [UNESP]; Rossingnoli, Nadia Oliveira; Pinho Costa, Katia Aparecida de; Prado, Renato de Mello [UNESP]; Gonzalez-Meler, Miquel; Martinez, Carlos Alberto (Elsevier B.V., 2021)
Tropical pastures play a significant role in the global carbon cycle and are crucial for world livestock production. Despite its importance, there is a paucity of field studies that clarify how tropical pasture species will be affected by environmental changes predicted for tropical regions. Using a temperature-free air-controlled enhancement (T-FACE) system, we increased canopy temperature (+2 degrees C over ambient) and evaluated the effects of warming under two soil moisture conditions in a factorial design over the physiology, forage production, and forage quality of a tropical forage legume, Stylosanthes capitata. Under well-watered conditions, warming increased the PSII efficiency, net photosynthesis, and aboveground biomass accumulation, but reduced forage quality and digestibility by decreasing crude protein content and increasing lignin content. Non-irrigated conditions under ambient temperature reduced leaf water status presumably promoting the reduction in net photosynthesis, forage production, and forage quality and digestibility. Under the combination of canopy warming and non-irrigated conditions, warming mitigated the effects of reduced soil moisture on leaf photosynthesis and biomass production, but a significant interaction reduced forage quality and digestibility more than under isolated treatments of warming or non-irrigated conditions. We found a potential physiological acclimation of the tropical forage species to moderate warming when grown under rainfed or well-watered conditions. However, this acclimation was achieved due to a trade-off that reduced forage nutritional value and digestibility that may impact future animal feeding, livestock production, and would contribute to methane emissions. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Climate change; Forage species; Legume; Photosynthesis; Stomatal conductance; Tropical climate; Warming